Sites of exuberance: Barry Barclay and Fourth Cinema, ten years on. (1st September 2015) - Milligan, Christina
The Ma-ori film-maker Barry Barclay used the term 'Fourth Cinema' to describe indigenous cinema, a philosophy based on his own practice as a director. He sought to privilege the indigenous gaze and the indigenous audience by centralizing te ao Ma-ori or the Ma-ori world-view in principle and in practice. However, much has changed in the world of film-making since Barclay developed his theory. The range of storytelling by Ma-ori on large and small screens has increased exponentially, and Ma-ori films such as Boy (Waititi, 2010) and Mt Zion (Kahi, 2013) have reached the top of the domestic box office, implying a wide Ma-ori and non- Ma-ori audience within the settler-centric culture of New Zealand. This article reviews and contextualizes Barclay's philosophy. It then uses his central concepts to examine the feature Mt Zion, exploring aspects of the film's text, production and distribution, to establish what conclusions can be drawn regarding the relevance of Barclay's thinking to the practice of a new generation of Ma-ori film-makers.